Influencia del recurso digital Human Anatomy Atlas en el aprendizaje de Anatomía Humana en segundo de Bachillerato de la UECIB “Priscila Baer”. - Guaranda Ramírez, Edwin Geovanny (2025)
Learning human anatomy has always been a challenge due to its theoretical complexity and the difficulty of clearly visualizing bodily structures. Today, three-dimensional technologies have revolutionized learning processes, offering tools that promote visual understanding and direct interaction with content. In this context, the present research entitled: Influence of the Human Anatomy Atlas digital resource on the learning of human anatomy in second-year high school students at the UECIB “Priscila Baer,” analysed the effectiveness of this digital resource in improving anatomical learning. The research was conducted using a quantitative approach and a pre-experimental design, applying pre and post-tests to assess the level of knowledge before and after the intervention, as well as a Likert-type survey to gauge student perception. The results showed a significant increase in academic performance and motivation toward the subject, demonstrating that the use of the Human Anatomy Atlas facilitated the understanding of complex anatomical structures and promoted active and interactive learning. In conclusion, the digital resource was consolidated as an innovative pedagogical tool that could strengthen the teaching and learning of human anatomy.